Spin‐Optoelectronic Phenomena for a Semitransparent Nonfullerene Photovoltaic System. Issue 7 (7th May 2021) - Zhao, Fenggui; Zhang, Jiahao; Zhang, Caixia; Li, Juqian; Zhang, Xiangpeng; Yu, Haomiao; Li, Jinpeng; Wang, Kai
Abstract : A unique feature of nonfullerene acceptors (NFAs) is their strong photoabsorption capability at longer wavelengths and electrostatic potentials (ESPs), which is expected to increase the photocurrent density ( J ) for bulk heterojunction (BHJ)‐based semitransparent organic solar cells (ST‐OSCs). Indeed, the interior spin‐optoelectronic phenomena are incredibly rich, and it remains challenging to correlate them with a complete photovoltaic process. Here, a prototypical PTB7‐Th: IEICO‐4F‐based ST‐OSC, with an average visible transmittance (AVT) of ≈26.8%, is fabricated for studying the issue (PTB7‐Th: poly[4, 8‐bis(5‐(2‐ethylhexyl)thiophen‐2‐yl)benzo[1, 2‐b;4, 5‐ b′ ]dithiophene‐2, 6‐diyl‐alt‐(4‐(2‐ethylhexyl)‐3‐fluorothieno[3, 4‐ b ]thiophene‐)‐2‐carboxylate‐2‐6‐diyl)]; IEICO‐4F: 2, 2 ′ ‐((2 Z, 2 ′Z )‐(((4, 4, 9, 9‐tetrakis(4‐hexylphenyl)‐4, 9‐dihydro‐sindaceno[1, 2‐ b :5, 6‐ b′ ]dithiophene‐2, 7‐diyl)bis(4‐((2‐ethylhexyl)oxy)thiophene‐5, 2‐diyl))bis(methanylylidene))bis(5, 6‐difluoro‐3‐oxo‐2, 3‐dihydro‐1 H ‐indene‐2, 1‐diylidene))dimalononitrile). Spin‐dependent electron–hole dissociation and charge transport dynamics are systematically studied in the dark condition, the short‐circuit current density ( J sc ) condition, and some intermediate stages by the nondestructive in situ magnetophotocurrent (magneto‐ J ) technique. Some intriguing mechanisms such as the Coulomb blockade–based bipolaron, the spin‐dependent polaron pair dissociation at charge transfer states (CTSs), and the triplet‐polaron reaction are extensively explored in the study. Despite these, the monochromatic light‐induced polarizability is validated to have a remarkable impact on the magnitude of the open circuit voltage ( V oc ). This work is completely devoted to the spin‐optoelectronic phenomena of the NFA‐based ST‐OSC in working condition. Abstract : A nonfullerene semitransparent organic solar cell with a high average visible transmittance of 26.8% is used for the study of spin‐dependent dissociation and charge transport dynamics.